Clinical Significance of TET2 in Female Cancers - Wan, Fang; Chen, Fangfang; Fan, Yangfan; Chen, Deqin (Frontiers in Bioengineering and Biotechnology, 2022)
Female cancers refer to malignant tumors of the female reproductive system and breasts, which severely affect the physical and mental health of women. Although emerging experiment-based studies have indicated a potential correlation between ten-eleven translocation methylcytosine dioxygenase (TET2) and female cancers, no comprehensive studies have been conducted. Therefore, this study aimed to summarize the clinical value and underlying oncogenic functions of TET2 in female cancers, such as breast invasive carcinoma (BRCA), cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), ovarian serous cystadenocarcinoma (OV), uterine corpus endometrial carcinoma (UCEC), and uterine carcinosarcoma (UCS), based on the data obtained from The Cancer Genome Atlas. The expression of TET2 was decreased in most female cancers, and its high expression was distinctly associated with the favorable prognosis of most female cancers. Furthermore, CD8+ T-cell infiltration was not correlated with TET2 in OV, UCEC, and UCS, whereas tumor-associated fibroblast infiltration was significantly correlated with TET2 in BRCA, CESC, and OV. TET2 was co-expressed with the immune checkpoint molecules ADORA2A, CD160, CD200, CD200R1, CD44, CD80, NRP1 TNFSF4, and TNFSF15 in most female cancers. Enrichment analysis revealed that some signaling pathways involving TET2 and related genes were related to tumorigenesis. Immunohistochemical and immunofluorescence staining confirmed the results of cancer immune infiltration analysis in BRCA tissues. Therefore, this study provides evidence for the oncogenic functions and clinical value of TET2 in female cancers.